Sustainability of retail store processes: an analytic model for economic and environmental evaluation. (17th May 2019) - Bottani, Eleonora; Casella, Giorgia; Arabia, Simona
This study proposes a model to evaluate the economic and environmental sustainability of retail stores. The model was developed under Microsoft Excel™ and reproduces the main retail store processes (i.e., product receiving, backroom storage, sales area management and return management) in quantitative terms. As input, the model takes several data about these processes; as output, it provides an evaluation of the total cost and CO2 emissions of the store. The application of the model to a real case, referring to a large-scale retail store of Italy, and the discussion of the key results obtained is presented for all the processes considered. The outcomes show that the most relevant environmental impact and the highest total cost are generated by the sales area management process. Conversely, the return management process contributes to the total cost to a limited extent. A sensitivity analysis was carried out to highlight the key aspect managers should focus on to improve the sustainability of the retail store. The results obtained provide useful guidelines for store managers to optimise the sustainability of their internal processes.